Smart tools for evaluating the performance of information products and services - Batjes-Sinclair, Karen (Technical Centre for Agricultural and Rural Cooperation, 2002)
This workshop recommended that further work should be done in the field to develop 'smart practices' which would facilitate the work of practitioners